Temporal analysis of hippocampal CA3 gene coexpression networks in a rat model of febrile seizures - Hatylas Azevedo; Nathália Amato Khaled; Paula Santos; Fernanda Bernardi Bertonha; Carlos Alberto Moreira-Filho (The Company of Biologists, 2018)
Complex febrile seizures during infancy constitute an important risk factor for development of epilepsy. However, little is known about the alterations induced by febrile seizures that make the brain susceptible to epileptic activity. In this context, the use of animal models of hyperthermic seizures (HS) could allow the temporal analysis of brain molecular changes that arise after febrile seizures. Here, we investigated temporal changes in hippocampal gene coexpression networks during the development of rats submitted to HS. Total RNA samples were obtained from the ventral hippocampal CA3 region at four time points after HS at postnatal day (P) 11 and later used for gene expression profiling. Temporal endpoints were selected for investigating the acute (P12), latent (P30 and P60) and chronic (P120) stages of the HS model. A weighted gene coexpression network analysis was used to characterize modules of coexpressed genes, as these modules might contain genes with similar functions. The transcriptome analysis pipeline consisted of building gene coexpression networks, identifying network modules and hubs, performing gene-trait correlations and examining changes in module connectivity. Modules were functionally enriched to identify functions associated with HS. Our data showed that HS induce changes in developmental, cell adhesion and immune pathways, such as Wnt, Hippo, Notch, Jak-Stat and Mapk. Interestingly, modules involved in cell adhesion, neuronal differentiation and synaptic transmission were activated as early as 1 day after HS. These results suggest that HS trigger transcriptional alterations that could lead to persistent neurogenesis, tissue remodeling and inflammation in the CA3 hippocampus, making the brain prone to epileptic activity.